Cross-Sectional Investigation of Acute Changes in Ultrasonographic Markers for Biceps and Supraspinatus Tendon Degeneration After Repeated Wheelchair Transfers in People With Spinal Cord Injury. (November 2016) - Hogaboom, Nathan S.; Huang, Bernice L.; Worobey, Lynn A.; Koontz, Alicia M.; Boninger, Michael L.
ABSTRACT: Objective: The objectives of this work were to investigate how wheelchair transfers influence acute changes in ultrasound markers for biceps and supraspinatus tendon degeneration and to determine how such changes correlate with transfer technique and demographic characteristics. Design: Participants underwent quantitative ultrasound examinations for markers of biceps and supraspinatus tendon degeneration (tendon width, echogenicity, variance, and contrast) before and after a stressful repeated-transfers protocol. The Transfer Assessment Instrument was completed for each participant to identify transfer skills. Linear regression tested whether demographics and transfer skills correlated with ultrasound measures. Results: Sixty-two wheelchair users with spinal cord injury were included (39 with paraplegia and 23 with tetraplegia). Biceps tendon width increased after repeated transfers ( P < 0.001). Participants with greater body weight experienced greater increases in biceps width after transfers (β = 0.109, P < 0.05). Skills evaluating body position relative to the target surface and safe and stable hand and arm positions affected changes in biceps and supraspinatus width and echogenicity ( P < 0.05). Conclusions: Repeated transfers caused measurable changes in biceps tendon width in a subset of participants. Changes in biceps and supraspinatus ultrasound measures were related to body weight and performance of specific transfer skills. Further testing is needed to confirm whether the clinical meaning of the observed relationships and whether using certain transfer skills and reducing body weight can attenuate the development of tendinopathy. Abstract : Supplemental digital content is available in the text.